THE PHENOMENON OF HUMAN LOVE IN THE CONTEXT OF PHILOSOPHICAL AND PSYCHOLOGICAL CONCEPTS - Rahimberganova Dinora Arslanbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Many issues that affect all people on a moral, ethical, social, and psychological level are a result of the contemporary urban and technological society. Humanity currently faces numerous pressing issues, such as maintaining human subjectivity as a whole as well as culture and true humanity—that is, an individual's moral, spiritual, distinctive, and value-integrity principle—in man. In this situation, education and upbringing are crucial because they shape generations and influence how they think, behave, and define their values. People's minds and souls are formed and influenced in many ways by education and upbringing, which are attributed to several fundamental mechanisms. Loving connections are among these methods.